(untitled) (Global Journal of Science Frontier Research, 2020)
The article proposes, within the framework of the new cosmological model, which includes superfluid dark energy and dark matter, to revise the Einstein’s "vacuum field equation" and, based on new astronomical observations, to refine the type and speed of gravitational waves. I note the need for further improve the LIGO and Virgo detectors for detecting longitudinal of gravitational waves. The article considers the Wakefield effect implemented in the AWAKE project for particle acceleration in the Large Hadron Collider as a mechanism for the possible acceleration of primary protons and spacecraft to superluminal speeds at the top of longitudinal gravitational waves in space. I suggest using the SMOLA plasma space engine to provide spacecraft energy in stationary and pulsed modes.